BINGKAI BERITA BENCANA LUMPUR LAPINDO DI MEDIA ONLINE - Tania Ayu Apsari (Jurnal Komunikasi dan Kajian Media, 2018)
Each media has a different way of packing a news before it is presented to audiences. The same event can be interpreted differently by the audience because the media can construct the same news in a different meaning. This can result in the framing of a news reporter. This study aims to analyze the frame of news conducted by online media metrotvnews.com and liputan6.com in packaging the second well drilling news by Lapindo mud. Researchers would like to see how the reporting framework of Lapindo Second Mud Disaster by metrotvnews.com and liputan6.com. This research uses the method of analysis of framing model by Robert N.Entmant with qualitative descriptive approach. This research is the analysis of news text, so researchers take the news drilling second Lapindo mud during the period of January 2016 from online portal metrotvnews.com and liputan6.com. The theory used is the political economy of the media and the media and the news of disasters. Keywords: lapindo mudflow, framing analysis, online media, disaster journalism theory, economic theory and media politics